What Is It Like to Be a Bass? Red Herrings, Fish Pain and the Study of Animal Sentience - Mason, G. J.; Lavery, J. M. (Frontiers in Veterinary Science, 2022)
Debates around fishes’ ability to feel pain concern sentience: do reactions to tissue damage indicate evaluative consciousness (conscious affect), or mere nociception? Thanks to Braithwaite’s discovery of trout nociceptors, and concerns that current practices could compromise welfare in countless fish, this issue’s importance is beyond dispute. However, nociceptors are merely necessary, not sufficient, for true pain, and many measures held to indicate sentience have the same problem. The question of whether fish feel pain – or indeed anything at all – therefore stimulates sometimes polarized debate. Here, we try to bridge the divide. After reviewing key consciousness concepts, we identify “red herring” measures that should not be used to infer sentience because also present in non-sentient organisms, notably those lacking nervous systems, like plants and protozoa (P); spines disconnected from brains (S); decerebrate mammals and birds (D); and humans in unaware states (U). These “S.P.U.D. subjects” can show approach/withdrawal; react with apparent emotion; change their reactivity with food deprivation or analgesia; discriminate between stimuli; display Pavlovian learning, including trace conditioning; and even learn simple instrumental responses. Consequently, none of these responses are good indicators of sentience. Potentially more valid are aspects of working memory, operant conditioning, the self-report of state, and forms of higher order cognition. We suggest new experiments on humans to test these hypotheses, as well as modifications to tests for ‘mental time travel’ and self-awareness (e.g. mirror self-recognition) that could allow these to probe sentience (since currently they reflect perceptual rather than evaluative, affective aspects of consciousness). Because ‘bullet-proof’ neurological and behavioural indicators of sentience are thus still lacking, agnosticism about fish sentience remains widespread. To end, we address how to balance such doubts with welfare protection, discussing concerns raised by key sceptics in this debate. Overall, we celebrate the rigorous evidential standards required by those unconvinced that fish are sentient; laud the compassion and ethical rigour shown by those advocating for welfare protections; and seek to show how precautionary principles still support protecting fish from physical harm.